An Exploratory Study of the Views of Supervision Strategies by Community Corrections Probationers in China. (January 2020) - Jiang, Shanhe; Zhang, Dawei; Irwin, Darrell D.; Yang, Can; Xing, Minhui
Offenders' attitudes toward supervision models are critical for the success of supervision practices in community corrections. It is surprising, however, that there is a general lack of research on offenders' attitudes toward supervision models or strategies in community corrections. Using a sample of 351 offenders serving community corrections in City W, China, the current study found that the majority of the respondents positively perceived rehabilitation supervision and the environmental supervision strategies. The punishment supervision strategy was supported by the respondents but with a lower degree, relative to the support for other supervision strategies. Institutional factors were the most important predictors of the offenders' attitudes.